Particularities of changes in microbial communities of chernozem podzolized under two-years application of herbicides different danger class - Rokityanskiy , A.B. (AgroChemistry and Soil Science, 2016)
The influence of herbicides Trophy 90 and Gezagard 500 belonging to two different classes of danger on the changes in microbial cenosis of chernozem podzolized during the growing season Zea mays L. variety «Elegy» was investigated. It was found that the application of soil herbicides for two years has different effects on on microbial cenosis of chernozem podzolized depending on the period of validity, the hazard class and rates of application of herbicide. It was found that the introduction of herbicides for two consecutive years is more pronounced suppression of microflora than a single application. It was found that the application of herbicides belonging to different danger class reduces the microorganisms belonging to nitrogen and phosphorus cycle at the end of the growing season. It was revealed that the double dose of acetochlor more negative effect on microbial cenosis of chernozem podzolized than double dose prometrin, but the opposite situation is observed at application of the recommended doses of these herbicides. Calculated coefficients oligotrophicity and mineralization showed that herbicides cause deterioration of the trophic regime of the soil and cause an increase in the intensity of mineralization processes in the soil, especially when they are used for two consecutive years. According to the parameters of the calculated index of microbiological transformation of soil organic matter there is a decrease in the intensity of the transformation of organic matter chernozem podzolized.